ANALISIS PERBANDINGAN KEMANDIRIAN KEUANGAN PADA PROVINSI ACEH (STUDI KASUS PADA KABUPATEN/KOTA INDUK DENGAN KABUPATEN/KOTA PEMEKARAN: Kemandirian Keuangan Daerah - Faisal Faisal; Hikalmi Hikalmi; Maisyuri Maisyuri; Nuriana Nuriana; M Quraisy; Refiyanda Refiyanda (Asia-Pacific Journal of Public Policy, 2023)
This study compares regional financial autonomy between five established regency governments and five newly established regencies or cities in Aceh Province between 2015 and 2020. Data analysis makes use of the descriptive statistical test and the comparative test. The study discovered that North Aceh District's regional financial autonomy in 2015, 2017, and 2019–2020 was instructive, whereas 2016 and 2018 were not. An advisory relationship is a collaborative and interactive relationship that entails advice, expertise, and The 2015–2020 instructive relationship pattern includes Lhokseumawe City, the South Aceh Regency, the Aceh Singkil Regency, the Bener Meriah Regency, the East Aceh Regency, and the Pidie Jaya Regency. The pattern of consultative relationships evaluates the fiscal autonomy of the Central Aceh District from 2015 to 2020. From 2015 to 2019, the relationship pattern in Langsa City was instructive. In contrast, consultative relationships extend from 2018 to 2020. The instructive relationship pattern encompasses Pidie Regency's regional financial autonomy in 2015–2017 and 2019–2020, whereas the consultative pattern encompasses 2018. North Aceh Regency and Lhokseumawe City have comparable regional financial independence. South Aceh District and Aceh Singkil District had comparable regional financial autonomy from 2015 to 2020. Central Aceh Regency and Bener Meriah Regency had distinct financial autonomy between 2015 and 2020. From 2015 to 2020, the fiscal autonomy of East Aceh Regency and Langsa City varied. Comparable regional financial autonomy exists between Pidie and Pidie Jaya between 2015 and 2020.